Theory of marketplace morality and impoverished consumers - Hill, Ronald Paul (Marketing Theory, 2018)
Morality related to the marketplace has been studied in interdisciplinary contexts as well as the marketing and consumer behavior domains. This research has resulted in prescriptions and proscriptions that seek to right what is perceived as wrongful marketer actions. Yet this work has had little influence on marketing theory. Thus, we seek to advance a marketplace morality theory within a consumer behavior frame, emphasizing treatment of the poor by actors who may or may not supply the goods and services necessary so that they can meet “consumption adequacy.” The article opens with a look at how this discussion has moved along a theoretical path. Implications for morality related to consumers in poverty come next, followed by blending of philosophical and consumer literatures to reveal a novel theoretical framework.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNDcwNTkzMTE3NzUzOTgz